Influence of D1, D2 Receptor Blockade in Basolateral Amygdala on Behavior of Rats with High or Low Levels of Anxiety and Fear - Pavlova, I V; Rysakova, M P; Sergeeva, M I (Zurnal vyss̆ej nervnoj dejatelnosti imeni I P Pavlova, 2015)
The influence of bilateral D1 or D2 receptors antagonists infusions into the rat basolateral amygdala on anxiety, as well as the expression, extinction and re-learning of conditioned fear was studied. Subjects were the male Wistar rats with high and low anxiety behavior in elevated plus maze, and also rats with low and high freezing responses during fear conditioning. The infusion of D1 receptor antagonist (SCH23390, 1 µg/0.5 µL in each side) reduced the expression of the conditioned fear to sound in rats with low freezing level, accelerated fear extinction and impaired re-learning in all animals. The injection of D2 receptor antagonist (raclopride, 1 µg/0.5 µL in each side) accelerated the extinction of conditioned fear to contextual cues in all rats and had a weak anxiolytic-like effect on behavior of high anxiety rats in elevated plus maze. These findings testify to the role of D1 receptors in the acquisition, expression and extinction of conditioned fear to stimuli, and D2 receptors in the occurrence of anxiety and fear to the contextual cues. There was discovered different sensitivity of animals with different levels of anxiety and fear to the infusion of dopamine receptors antagonists in the amygdala that suggested the inequality of dopaminergic transmission in the amygdala of animals with individual differences.